AGE-RELATED PHARMACOKINETIC AND PHARMACODYNAMIC VARIABILITY: CLINICAL IMPLICATIONS IN PEDIATRIC AND GERIATRIC COHORTS (World Bulletin of Public Health, 2026)
The physiological evolution of the human body across the lifespan dictates profound shifts in drug disposition and target organ sensitivity. This study evaluates the precise age-dependent pharmacokinetic and pharmacodynamic parameters influencing therapeutic efficacy and adverse drug reaction rates in extreme age brackets. A prospective observational cohort study was conducted involving 245 subjects, stratified into pediatric (n=110, ages 1-12 years) and geriatric (n=135, ages >65 years) groups, to assess renal clearance anomalies and hepatic cytochrome P450 enzyme efficiency. Clinical data indicate a paradoxical physiological divergence; the geriatric cohort demonstrated a 34.2% mean reduction in glomerular filtration rate, directly correlating with prolonged elimination half-lives of hydrophilic medications, whereas the pediatric cohort exhibited accelerated phase I hepatic metabolism. Statistical analysis revealed a high incidence of polypharmacy-induced toxicity in the elderly (p = 0.012), juxtaposed against subtherapeutic dosing outcomes in pediatric patients due to enhanced hepatic extraction ratios. The dynamics of the observed results suggest that empirical dosage regimens, traditionally standardized for healthy adults, fail significantly when extrapolated to vulnerable age groups. Individualized pharmacological profiling, adjusting for total body water compartmentalization and age-specific receptor affinity, remains an absolute requirement to optimize clinical outcomes and mitigate iatrogenic risks.
Keywords: Clinical pharmacology; pharmacokinetics; pharmacodynamics; geriatric polypharmacy